Pengaruh Model Problem Based Learning dan Motivasi Belajar Terhadap Hasil Belajar Siswa Sekolah Dasar - Nurmalasari, Yulia; Padlurrahman, Padlurrahman; Wazni, Muhammad Khairul (Jurnal Ilmiah Global Education, 2025)
This study aims to determine the influence of the Problem Based Learning (PBL) learning model and learning motivation on the English learning outcomes of elementary school students. This study uses a quantitative approach with a posttest-only control group design quasy experiment type. The research sample consisted of 60 grade V students of SDN 3 Selong which were divided into 2 groups, namely the experimental group using the PBL model and the control group using conventional learning. The research instruments include a learning motivation questionnaire and a learning outcome test. Data analysis was carried out through normality tests, homogeneity tests, and two-lane ANOVA tests. The results showed that 1) the Problem-Based Learning (PBL) Model was proven to be significantly more effective in improving students' English learning outcomes compared to conventional learning, 2) There was an effect of interaction between problem-based learning and motivation on students' English learning outcomes, 3) for students who had high motivation, the learning outcomes of English subjects learned with problem-based learning were higher than that of students who were learned conventionally, 4) for students who have low motivation, the English learning outcomes learned with problem-based learning are lower than those learned conventionally. The implications of these findings show the importance of implementing innovative learning models that take into account the motivational characteristics of students.